Synthesis, structural studies, and antibacterial activity of zinc, copper, and silver complexes derived from N′-(1-(pyrazin-2-yl)ethylidene)isonicotinohydrazide. Issue 5 (4th March 2017) - Zhao, Shan-Shan; Wang, Peng; Wang, Li-Na; Fu, Lin; Han, Xiao-Meng; Qin, Jie; Qian, Shao-Song
Abstract: The multidentate Schiff-base ligand N′-(1-(pyrazin-2-yl)ethylidene)isonicotinohydrazide (HL ) has been prepared. Reaction with zinc, copper, and silver nitrate afford three complexes, [Zn(HL′ )2 ](NO3 )2 ·3H2 O (1 ), [Cu2 (L )2 (NO3 )(H2 O)2 ]·NO3 n (2 ) and [Ag2 (L )2 ]·3H2 On (3 ). These complexes have been characterized by elemental analysis, IR spectroscopy, and single-crystal X-ray diffraction. In1, HL is a neutral tridentate ligand, whereas in2 and3, HL is a deprotonated tetradentate ligand. The hydrogen bonding interactions between NO3 − and the host framework result in various supramolecular polymeric structures: a 2-D layer for1 and 3-D network for2 and3 . The antibacterial activities of these complexes have been investigated and the results indicate that3 showed good antibacterial activities. Abstract :